RELIGIOUS SONGS TRANSLATION IN POST-PANDEMIC ERA: COMPARING THE TRANSLATION METHODS DONE BY HUMAN AND MACHINE (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2021)
The interaction of every individual in this world has always become a part of human beings. There comes a pandemic era caused by a virus known as Covid-19. It takes over most of the human interactions. This virus causes social distancing, where people are not allowed to meet each other and have direct contact. Human beings need technology to come to the rescue. Machine translation has come to the surface to help and loosen everyone’s burden in translating foreign songs since it works instantly for less than a minute and can be done everywhere through the gadget. However, machine translation could not be trustworthy for translating because it is programmed to translate words independently. The purpose of this paper is to try to compare the translation methods done by humans and machines in translating religious songs. Religious songs are composed within poetry in their lyrics and intended to deliver worship with deep meaning. Therefore, in prayerful song translation, the significance is prioritized, although singing ability and translation must also be thought-through since songs are for performance. The methods used by humans and machines lead to the performability and singing ability of the song translation.